PERFORMANCE EVALUATION OF HEAVY EQUIPMENT IN THE JAKARTA LRT PHASE 1B PROJECT - BILHAN GAMALIEL HARTANTO (CV KULTURA DIGITAL MEDIA, 2025)
Infrastructure projects, particularly in the development of mass transportation systems such as light rail transit (LRT), are highly dependent on the role of heavy equipment. The use of heavy equipment is a determining factor in the success of specialized rail transportation development, where the production capacity of heavy equipment plays a major role in influencing project progress. Therefore, an analysis of production volume capacity is essential. This study aims to evaluate production volume capacity in the Jakarta LRT Phase 1B project, including an analysis of the capacity of cranes, excavators, dump trucks, compactors, and other heavy equipment. Volumetric methods were applied to calculate the volume capacity and productivity of heavy vehicles. The analysis results show that the calculated volume and productivity of heavy equipment have met the targets in accordance with the established schedule.